BFGF ameliorates intestinal mucosal permeability and barrier function through tight junction proteins in burn injury rats. Issue 5 (August 2021) - Jiang, Yan; Zhang, Caifeng; Wang, Tingli
Highlights: The effect of bFGF on intestinal permeability in vivo was studied. There was a close association with bFGF and TJPs in burn injury. BFGF injection could ameliorate intestinal mucosal permeability in burn injury rats. Abstract: Backgroud: To investigate the protective effect of exogenous basic fibroblast growth factor (bFGF) treatment on the intestinal mucosa in scalded rats. Methods: Thirty-six SD rats were randomly divided into 3 groups (n = 12): sham group, scald group and bFGF group (0.5 mg/kg). Intestinal barrier dysfunction was evaluated by permeability of intestinal mucosa to fluorescein isothiocyanate (FITC)-dextran and Chiu's grading system. H&E staining was used to detect the morphological changes of intestinal mucosa. Immunohistochemistry was used to observe zonula occludens-1 (ZO-1) and occludin. Western blot assay was used to detect the expression of ZO-1, Claudin-1, occludin and myosin light-chain kinase (MLCK). Results: The results demonstrated that following bFGF treatment, permeability of the intestinal epithelium barrier of was significantly decreased compared to scald group. H&E staining and Chiu's grading were consistent with previous result. The expression of ZO-1, Claudin-1, occludin in bFGF group were significantly increased compared to scald group, while MLCK protein was decreased. Conclusions: bFGF ameliorates permeability of intestinal mucosa after burns. The possible mechanism may be relate to bFGF could increase the expression level of tight junction proteins (TJPs).